Sundays : a cookbook - Godwin, Sophie (Crows Nest, NSW : Murdoch books, an imprint of Allen & Unwin, 2023)
"Sundays are special. Yes, sometimes we might feel like we're slowly dying because of the night before, yet even then, there's joy to be had in the ravenous hunger, copious carbs, and the legitimacy of binge-watching a TV show, especially if the weather is dreary. Other times, Sunday is about sharing, feasting with friends, BBQing, leisurely long lunches or brunches because it's the one day of the week when mealtimes are flexible. Or perhaps it's a Sunday reset, the self-love of a bath, book, and a big plate of greens." -- Publisher.
Includes index.
Title from title screen.
Also available in print.
Mode of Access: Available online.
Keywords: Cooking; Electronic books; Cookbooks